Phase-locked loops : system perspectives and circuit design aspects - Rhee, Woogeun; Yu, Zhiping (Hoboken, New Jersey : Wiley-IEEE Press, 2023)
'This book gives insight into how to design phase-locked loops (PLLs) to meet different system requirements. Learning system architectures and design trade-offs, readers will know where to, when to, and how to use PLLs for broad range of applications. The organization of the book is unique in that the fundamental theories and the circuit design aspects are well balanced for PLL circuit design. From this book, readers learn the role of PLLs in modern communication systems, phase-lock techniques, and theoretical analysis of PLL. Other areas covered include system design considerations and architectures, building blocks with practical circuit design aspects, applications of PLLs for wireless and wireline systems, and advanced topics such as noise coupling, layout, etc.'--
Includes index.
Keywords: Phase-locked loops